2013
DOI: 10.1002/chem.201301096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1‐Substituted Tetrahydroisoquinolines by Lithiation and Electrophilic Quenching Guided by In Situ IR and NMR Spectroscopy and Application to the Synthesis of Salsolidine, Carnegine and Laudanosine

Abstract: The lithiation of N-tert-butoxycarbonyl (N-Boc)-1,2,3,4-tetrahydroisoquinoline was optimized by in situ IR (ReactIR) spectroscopy. Optimum conditions were found by using n-butyllithium in THF at -50 °C for less than 5 min. The intermediate organolithium was quenched with electrophiles to give 1-substituted 1,2,3,4-tetrahydroisoquinolines. Monitoring the lithiation by IR or NMR spectroscopy showed that one rotamer reacts quickly and the barrier to rotation of the Boc group was determined by variable-temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 95 publications
1
22
0
Order By: Relevance
“…This result indicates that the rotation of the Boc group is slow at -78 °C, but fast at -50 °C, in line with previous work. 4,7 The n-BuLi coordinates to the carbonyl oxygen atom of the Boc group (sometimes referred to as a 'complex induced proximity effect'), 6 so for benzylic lithiation to occur in high yield the Boc group must rotate under the conditions of the reaction. Please do not adjust margins Please do not adjust margins …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This result indicates that the rotation of the Boc group is slow at -78 °C, but fast at -50 °C, in line with previous work. 4,7 The n-BuLi coordinates to the carbonyl oxygen atom of the Boc group (sometimes referred to as a 'complex induced proximity effect'), 6 so for benzylic lithiation to occur in high yield the Boc group must rotate under the conditions of the reaction. Please do not adjust margins Please do not adjust margins …”
Section: Resultsmentioning
confidence: 99%
“…1). 4 Here we demonstrate that the chemistry is amenable to other substituted tetrahydroisoquinolines and to a variety of different electrophiles, leading to its application to the syntheses of the alkaloids (±)-crispine A and (±)-dysoxyline.In our earlier work we showed that the Boc group in N-Boctetrahydroisoquinoline rotates slowly at -78 °C. 4 As the lithiation at the 1-position is directed by complexation of the base (n-butyllithium) with the carbonyl of the Boc group, 6 better yields can be obtained at -50 °C since the Boc rotation is faster.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…While tetrahydroquinoline gave low yield (20%), tetrahydroisoqinoline is arylated exclusively at the C-3 position in good yield and excellent enantioselectivity ( 2g ). It is worth noting that under lithiation conditions, the functionalization will occur at the more acidic C-1 position 32 . Considering the broad utility of acyclic chiral amines in organic synthesis, we attempted asymmetric C–H arylation of N,N -diethyl- and N,N -ethylbutyl-amines.…”
mentioning
confidence: 99%
“…was treated with n BuLi (2.36 mmol, 1.1 equiv.) in THF (10 mL) at –50 °C under nitrogen atmosphere . The dark red colored solution so obtained was stirred at this temperature for 30 min.…”
Section: Resultsmentioning
confidence: 99%